Influence of Ti and Fe doping on the structural and electrochemical performance of LiCo0.6Ni0.4O2 cathode materials for Li-ion batteries. Issue 20 (15th October 2022) - Azahidi, A.; Kasim, M.F.; Elong, K.; Kamarulzaman, N.; Mastuli, M.S.; Rusop, M.
Abstract: The combination of lithium cobalt oxide (LCO) and lithium nickel oxide (LNO) property for Li-ion batteries (LIB) brings a very promising cathode material, LiCo1−x Nix O2 with a high specific reversible capacity and good cycling behaviour. Nonetheless, high toxic Co content and an instability of Li + /Ni 2+ interaction in LiCo1−x Nix O2 crystal structure paved the way for some modification for the development of this potential material. In this research, the self-propagating combustion method is used to reduce 40% Co content of LCO by replacing it with 40% Ni content resulting in cathode material with the stoichiometry of LiCo0.6 Ni0.4 O2 (LCN). To improve the stability of the LiCo0.6 Ni0.4 O2 structure, 5% of Ti and Fe was substituted at the Co site of the LCN material. The effect of these different cation substitutions (Ti 4+ and Fe 3+ ) on the structural and electrochemical performance of layered LiCo0.6 Ni0.4 O2 cathode materials was investigated. Rietveld refinement revealed that Fe doped material has the longest atomic distance Li–O in the structure that allow better Li + diffusion during intercalation/deintercalation to give an excellent electrochemical performance (138 mAhg −1 ). After 50th cycle, it is found that the discharge cycling for Ti and Fe substituted materials were improved by more than 5% compared to pristine material. Both Ti and Fe doped materials were also having less than 13% of capacity fading indicates that the substitution of some Co with Ti and Fe are stable and can retain their electrochemical properties.